Assessment Of Financial Performance at PT. Bank Tabungan Negara (Persero) Tbk Using The Dupont System Method Period 2019-2021 - Idris, Abdi Akbar; Hasbiah, Siti (Economics and Business Journal (ECBIS), 2023)
Appraisal of a company's performance can be seen both through financial and non-financial aspects. This study specifically measures financial performance by focusing on DuPont System analysis. The DuPont system divides performance into three components, namely net profit margin, rate of return on assets, and rate of return on equity/capital. However, in this study, only two components of the DuPont System were used, namely return on assets and net profit margin. This type of research is quantitative research with a descriptive approach. The data analyzed comes from the financial reports at PT. State Savings Bank (PERSERO) Tbk specifically in the statement of financial position and annual comprehensive income statement ending December 31 2019 to December 31 2021. The results of the study show that Bank BTN has low financial performance. Judging from the total ROA generated each year, it cannot reach the standard set by Bank Indonesia. Even though it has a low ROA value, Bank BTN is able to increase ROA from year to year.